2012
DOI: 10.1002/hipo.22008
|View full text |Cite
|
Sign up to set email alerts
|

Voltage dependence of subthreshold resonance frequency in layer ii of medial entorhinal cortex

Abstract: The resonance properties of individual neurons in entorhinal cortex may contribute to their functional properties in awake, behaving rats. Models propose that entorhinal grid cells could arise from shifts in the intrinsic frequency of neurons caused by changes in membrane potential due to depolarizing input from neurons coding velocity. To test for potential changes in intrinsic frequency we measured the resonance properties of neurons at different membrane potentials in neurons in medial and lateral entorhina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 65 publications
(120 reference statements)
5
38
0
Order By: Relevance
“…We provide clear evidence that differences in AP waveform between SCs and FCs in adult mice determine the differences in firing regularity and frequency, both of them significantly increased in SCs. In good agreement with data from rat brain slices [37], we found that the rheobase of FCs is significantly lowered, mainly because of the higher resting membrane resistance, indicating that these neurons are more prone to repetitive firing than SCs. On the other hand, during maximal current injection, SCs initially fire at higher frequency than FCs, but adapt more rapidly to steady-state frequencies.…”
Section: Discussionsupporting
confidence: 88%
“…We provide clear evidence that differences in AP waveform between SCs and FCs in adult mice determine the differences in firing regularity and frequency, both of them significantly increased in SCs. In good agreement with data from rat brain slices [37], we found that the rheobase of FCs is significantly lowered, mainly because of the higher resting membrane resistance, indicating that these neurons are more prone to repetitive firing than SCs. On the other hand, during maximal current injection, SCs initially fire at higher frequency than FCs, but adapt more rapidly to steady-state frequencies.…”
Section: Discussionsupporting
confidence: 88%
“…To address these data, electronic supplementary material, figure S1 ( parts A,B,C) shows the circuit simulated using parameters matching the slower resonance frequency of a cell in bat medial entorhinal cortex [52], as simulated in figure 1d(i)(ii). For comparison, electronic supplementary material, figure S1 part D shows the circuit model with the parameters of theta frequency resonance from figure 2 (and figure 1c(i)(ii)) that match rat dorsal medial entorhinal cortex [31,37]. The models show the same functional ability to switch between different phases of activity, as long as the frequency of medial septal input is altered to be close to the frequency based on the intervals between rebound depolarizations.…”
Section: Periodicity With Both High and Low Resonance Frequenciesmentioning
confidence: 99%
“…The strong inhibitory innervation of stellate cells coupled with their intrinsic properties suggests a functional role for rebound spiking. Rebound spikes occur in response to release from hyperpolarizing current pulses and are dependent on the presence of the h-current ( I h , Alonso & Llinás, 1989; Klink & Alonso, 1993; Shay, Boardman, James, & Hasselmo, 2012). Recent models have simulated grid cell firing behaviors using phase interactions between theta oscillations and stellate cell rebound spikes (Hasselmo, 2013; Hasselmo & Shay, 2014).…”
Section: Introductionmentioning
confidence: 99%